The exhibition at the Balti Scientiﬁc Library “Divout and hard-working people... " German settlers in Bessarabia (1814-1940) (Confluenţe Bibliologice, 2013)
The article is about Germans colonies in Bessarabia. German colonization of Bessarabia began in 1812 when Russia acquired this territory from the Ottoman Empire. Tsar Alexander I. issued an invitation to Germans - mainly in the Duchy of Warsaw - to settle in this region. These Germans had migrated there from several German states - especially Prussia, Wurttemberg and Baden - to colonize the Prussian districts after the ﬁrst partition of Poland. After 125 years they had displaced. Through this exhibition “Divout and hard-working people..." German settlers in Bessarabia (1814-1909)”, organizers try to relate not only the rich history  in events of this people, but reﬂects their daily life in community, their way of managing, culture, as well as their relationship with the other ethnic groups.
Keywords: thematic exhibition; history of Bessarabia